How Banks Respond to Negative Interest Rates: Evidence from the Swiss Exemption Threshold - Christoph Basten; Mike Mariathasan (Center for Economic Studies and ifo Institute (CESifo), 2018)
We analyze the effect of negative monetary policy rates on banks, using detailed supervisory information from Switzerland. For identification, we compare changes in the behavior of banks that had different fractions of their central bank reserves exempt from negative rates. More affected banks reduce costly reserves and bond financing while maintaining non-negative deposit rates and larger deposit ratios. Higher fee and interest income successfully compensates for squeezed liability margins, but credit and interest rate risk increase. Portfolio rebalancing implies relatively more lending, also compared to an earlier rate cut within positive territory, and risk-taking reduces regulatory capital cushions and liquidity.
Keywords: E43; E44; E52; E58; G20; G21; 330; monetary policy transmission; negative interest rates; bank profitability; risk-taking; bank lending; Basel III